Review of Mathematica's Problem Solving Implementation in Elementary School - Indri Anugrahaeni; Haryanto Haryanto (UM Purwokerto Press, 2023)
Problem solving is the ability of students to solve problems through a systematic thinking process. This research is focused on the implementation of problem solving, especially in elementary schools. This review summarizes the findings of literature studies on problem solving in elementary schools that were published from 2016-2022. Researchers use systematic. First of all the researcher formulates a research problem, then proceeds to explore relevant articles related to problem solving in elementary schools for analysis. Articles were searched using Scopus, Science Direct. From the search results obtained 142 articles related to problem solving. The results of the review revealed that 51% of the articles were the implementation of problem solving in elementary schools and 40 relevant articles were obtained.